Effects of white vinegar on Carbohydrate Contents in Hepatorenal Tissues in Rats. - Alshailabi, Eda M. A. (Scientific Journal for Faculty of Science-Sirte University, 2021)
White vinegar is mildly acidic with a pH of 2-3 that has long been used as a relish and traditional medication that depends on its concentration. Yet even a small amount of white vinegar in a small concentration may cause serious poisoning. Recently, many sorts of white vinegar have been developed using fundamental sources and technologies to satisfy customer needs. This study was aimed to investigate the effects of white vinegar on carbohydrate contents in hepatorenal tissues in rats. Thirty female rats were used, they were divided into three groups, group 1 was given distilled water as the normal control group, group 2 was given white vinegar with a dose (1 ml/kg (5 %)) and group 3 was given white vinegar with a dose (1 ml/kg (10 %)) for two weeks. PAS stain in all treated tissues showed a decrease in carbohydrate contents when compared with the control group. In conclusion, white vinegar consumption has adverse effects on carbohydrate contents in hepatic and renal tissues in rats, hence the quantity of white vinegar should be discouraged or reduced.